2007
DOI: 10.1007/bf02932135
|View full text |Cite
|
Sign up to set email alerts
|

Colony density influences invasive and filamentous growth inSaccharomyces cerevisiae

Abstract: The effect of colony density on the dimorphic switch was determined in natural strains of Saccharomyces cerevisiae. In some strains invasiveness and pseudohyphal (PH) growth were highly sensitive to colony density; moreover, strains constitutively able to invade the substrate with PH formation positively influenced the invasiveness but not the PH growth of a different strain less prone to the dimorphic switch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A recent study of Lucaccioni et al (2007) has shown that the colony density positively influenced invasive growth and pseudohyphal formation in some natural strains of S. cerevisiae. However, strains constitutively able to invade the substrate and with pseudohyphal growth positively influenced the invasiveness but not the pseudohyphae formation of a different strain less prone to the dimorphic switch.…”
Section: Functional and Biotechnological Significance Of Filamentatiomentioning
confidence: 99%
“…A recent study of Lucaccioni et al (2007) has shown that the colony density positively influenced invasive growth and pseudohyphal formation in some natural strains of S. cerevisiae. However, strains constitutively able to invade the substrate and with pseudohyphal growth positively influenced the invasiveness but not the pseudohyphae formation of a different strain less prone to the dimorphic switch.…”
Section: Functional and Biotechnological Significance Of Filamentatiomentioning
confidence: 99%